Dominant Factors of Compliance With Health Protocol Implementation During The Covid-19 Pandemic at Tourism Place in Jambi City - Fitria Eka Putri; Vinna Rahayu Ningsih; Yuliana .; Hubaybah .; Adelina Fitri; Fajrina Hidayati6; M Rifqi Azhary (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Abstract The current handling of COVID-19 in Indonesia has entered a new phase, namely the new normal. This condition allows people to return to productive lives, while still complying with health protocols. Tourist attractions have the potential to become the locus of the spread of COVID-19 if there is a gathering of visitors while traveling, it is necessary to comply with the application of health protocols in order to break the chain of transmission of COVID-19. The emergence of the term Revenge Tourism or revenge tourism after the new normal was implemented, during the pandemic people felt bored doing activities at home until when there was a new policy, traveling was a way to reduce boredom while at home. The type of research used is observational with a cross sectional design. This study aims to determine the relationship between knowledge, trust and facilities with compliance with the application of health protocols during the COVID-19 pandemic at tourist attractions in Jambi City, the study was conducted at tourist attractions in Jambi City in June-August 2022. The population in this study are visitors to tourist attractions as many as 378 people. The minimum sample size is 345 people. Sampling using accidental random sampling method. Data were obtained through interviews with a questionnaire instrument. The data is processed using a computer device and then analyzed descriptively and analytically. The results of the statistical test showed that there was a significant relationship between knowledge (p = 0.007), trust (p = 0.000) and facilities (p = 0.003) with compliance with the application of health protocols during the covid-19 pandemic in tourist attractions in Jambi City.